2014
DOI: 10.5565/rev/jtl3.539
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ First Language Use in Second Language Learning Classroom Context: A Questionnaire-based Study

Abstract: Recently the issue of having recourse to second language (L2) learners' first language (L1) in second language acquisition (SLA) is receiving a great amount of attention in SLA research. There has been a great deal of claims and counterclaims with respect to L1 use in L2 learning. The findings of L2 research to date cast doubt on the rationales of proponents of exclusive use of L2. To date, L2 researchers and practitioners have observed L2 classrooms and have come up with different functions of L1 in L2 learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
47
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 41 publications
7
47
0
2
Order By: Relevance
“…Moreover, Kharma and Hajjaj (1989) found that 66% of their teacher-participants believed that L1 should be used in order to explain L2 grammar. Similar findings were reported by Al-Shammari, (2011), Bateman, (2008), Mohebbi and Alavi, (2014), and Sharma (2006).…”
Section: Metalinguistic Usesupporting
confidence: 91%
See 4 more Smart Citations
“…Moreover, Kharma and Hajjaj (1989) found that 66% of their teacher-participants believed that L1 should be used in order to explain L2 grammar. Similar findings were reported by Al-Shammari, (2011), Bateman, (2008), Mohebbi and Alavi, (2014), and Sharma (2006).…”
Section: Metalinguistic Usesupporting
confidence: 91%
“…In other words, learners' will tend to make links between the L1 and L2 in order to learn the L2 because "the two languages are closely linked in the mind" (Cook, 2001, p. 414 Sharma (2006) found that 42% of participating teachers used their L1 in order to define new L2 vocabulary items. A similar finding was reported by Al-Shammari, (2011), Kharma and Hajjaj (1989), Mohebbi andAlavi (2014), andShweers (1999).…”
Section: Translationsupporting
confidence: 90%
See 3 more Smart Citations